Efficacy and Safety of Bempedoic Acid in Patients with High Cardiovascular Risk: An Update - Caklili, Ozge T.; Rizzo, Manfredi; Cesur, Mustafa (Current Vascular Pharmacology, 2024)
Statins play a significant role in the prevention of cardiovascular (CV) diseases (CVDs); however, non-adherence with statin treatment or statin intolerance (mainly attributed to muscleassociated side effects) is not uncommon. New agents such as bempedoic acid (BA) can provide more treatment options. BA is administered orally, once daily, at a dose of 180 mg in current clinical practice. It can decrease circulating low-density lipoprotein cholesterol (LDL-C) levels by nearly 30% as monotherapy or by 20% as an add-on to statins. CV outcome studies have shown that BA decreases major adverse CV event risk in patients with established CVD or high CV risk by 13%. When patients with high CV risk were analyzed alone, the risk reduction was 30%. Its side effects include a rise in serum uric acid levels and liver enzyme activity, whereas it does not increase diabetes risk as statins do. BA can be used as adjunctive therapy to statins in patients at high CV risk in whom lipid targets cannot be achieved or as an alternative to statins in patients with statin intolerance.
Keywords: statins